Dampak Tingginya Prevalensi TRICHURIS TRICHIURA Terhadap Kebijakan Pengobatan Massal Kecacingan Di Tiga SD di Kabupaten Tanah Bumbu - Paisal; Budi Hairani; Erly Haryanti; Listiana Indriyati (Jurnal Kebijakan Pembangunan, 2017)
Soil transmitted helminth (STH) is a neglected parasitic disease with a high prevalence in the world. The prevalence of STH in elementary school children in Indonesia was 31.8%, while the prevalence of STH for Tanah Bumbu District was 56.6%, with the most common species was T. trichiura (81%). The objectives of this study were to obtain STH prevalence rates for schoolchildren in SD Juku Eja, SD Sungai Lembu and SD Sepunggur, and to assess the conformity of the Ministry of Health's mass deworming policy with the most prevalence of worm species. The study was conducted in February 2015. The sample of the study was all elementary school students of class I-VI in selected schools. Fecal examination using the direct method. The statistical test using chi square test between the variables of worm infection and the variable of schools. Respondents were 348 people and a third (35.1%) were worm infected. Among the three schools, primary school with the highest infection regardless of worm species was SD Juku Eja (77%) followed by SD Lembu River (15.6%). There was a significant difference between the prevalence of worms for each elementary school. Among the 122 respondents who suffered from worms, 49.2% were single infections of T. trichiura. The mass deworming guidelines released by the Ministry of Health are slightly different from the effective treatment for T. trichiura infection, ie on the number of days of administration. In the Ministry of Health's mass deworming guidelines, albendazole was given a single dose while the specific treatment of T. trichiura infection, albendazole was given 3 times for 3 consecutive days. Because the dominant infection at this study was T. trichiura, it is recommended to change the dose of albendazole treatment in the mass treatment, from single dose administered to 3 times for 3 consecutive days. Abstrak Kecacingan merupakan penyakit parasit terabaikan yang banyak diderita oleh penduduk dunia. Prevalensi pada anak sekolah dasar di Indonesia sebesar 31,8%. Sedangkan untuk Kabupaten Tanah Bumbu, prevalensi kecacingan mencapai 56,6% dan spesies yang paling banyak ditemukan adalah T. trichiura (81%). Tujuan penelitian ini adalah mendapatkan data prevalensi kecacingan pada anak sekolah di SD Juku Eja, SD Sungai Lembu, dan SD Sepunggur, Kabupaten Tanah Bumbu, kemudian menilai kesesuaian kebijakan pengobatan massal kecacingan Kementerian Kesehatan dengan prevalensi spesies cacing yang paling banyak ditemukan. Penelitian dilakukan pada Februari 2015. Sampel penelitian adalah seluruh siswa SD kelas I-VI di sekolah terpilih. Pemeriksaan tinja menggunakan metode langsung. Uji statistik menggunakan uji chi square antara variabel status kecacingan dengan variabel tempat bersekolah. Responden sebanyak 348 orang dan sepertiganya (35,1%) positif kecacingan. Dari ketiga sekolah, SD yang memiliki infeksi paling tinggi tanpa memandang spesies cacing adalah SD Juku Eja (77%) disusul SD Sungai Lembu (15,6%). Terdapat perbedaan bermakna antara kejadian kecacingan untuk setiap SD. Dari 122 orang responden yang mengalami kecacingan, sebanyak 49,2% adalah infeksi tunggal T. trichiura. Pedoman pengobatan massal kecacingan yang dikeluarkan oleh Kementerian Kesehatan sedikit berbeda dengan pengobatan efektif untuk infeksi T. trichiura, yaitu pada jumlah hari pemberian. Pada pedoman pengobatan massal Kementerian Kesehatan, albendazol diberikan dosis tunggal sedangkan pengobatan spesifik infeksi T. trichiura albendazol diberikan 3 kali selama 3 hari berturut-turut. Karena infeksi dominan di lokasi penelitian adalah T. trichiura, disarankan untuk mempertimbangkan dosis pengobatan albendazol pada pengobatan massal, dari pemberian dosis tunggal menjadi pemberian sebanyak 3 kali selama 3 hari berturut-turut.